CLINICAL PHARMACOLOGY OF THE USE OF HEPATOPROTECTIVE DRUGS IN CHRONIC VIRAL INFECTIOUS DISEASES - Rasulov Bobur Abduqakhorovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article presents a comprehensive analysis of the clinical pharmacology of hepatoprotective drugs used in the management of chronic viral infectious diseases, particularly chronic hepatitis B and C. It explores the pharmacodynamic principles, mechanisms of hepatic protection, and the pharmacokinetic behavior of major hepatoprotective agents. The discussion extends to the role of antioxidant, membrane-stabilizing, antifibrotic, and immunomodulatory agents in the restoration of hepatic function under chronic viral injury. Given that the liver is a vital organ responsible for detoxification, metabolism, and protein synthesis, maintaining hepatocellular integrity in chronic viral infections is critical to improving long-term survival and quality of life. The paper emphasizes the importance of combining antiviral therapy with hepatoprotective treatment to achieve comprehensive management of hepatic pathology.